“Diseño de una planta de tratamiento de aguas residuales provenientes de los procesos de ósmosis inversa y generación eléctrica, para su posterior reutilización en la central termoeléctrica Quevedo II.” - Chiluiza García, Freddy Giovanny (2016)
This research project aims to design a treatment plant industrial wastewater, in order to reuse this valuable resource from the reverse osmosis processes and power generation in thermal power plants. The investigation is justified because now fresh water is decreasing by improper use of man, it being thus encourage sustainable management of it, representing a challenge in preserving the planet for mechanical engineers of the new century. The analysis of wastewater generated by the thermoelectric plant Quevedo II, is carried out to determine the parameters out of range to be covered, and determine the parameters to meet according to the TULAS standard for water use and discharge. Information concerning the nature of the project from different sources is reviewed to understand the workings of the physical processes of wastewater treatment, so you can familiarize yourself regarding the different technologies available. A flowchart is performed to determine the equipment, components and accessories necessary to conform the treatment plant, also this diagram will be clear to the distribution of equipment and what their operation. Later knowledge regarding fluid mechanics are applied to dimension the treatment plant, determining the flow to be handled within it, and how you will implement each treatment team for a suitable product. the selection procedures of equipment, components and accessories, which will make up the treatment plant wastewater are specified, and the project cost is determined.